Von der Freundschaft im Alten Testament und Alten Orient - Dietrich, Jan (Die Welt des Orients, 2014)
As many examples from the Old Testament and the Ancient Near East show, friendship is not fenced in by lineage but goes beyond the narrow limits of kinship-ties. Its virtue lies in loyalty, reliability, and trustworthiness ('œmûnāh and comparable terms) between friends. Since friendship, as a rule, develops between equals, friendship with God is rare, but is still found in the ancient sources. The article ends with a short discussion of Ben Sira's view on friendship and with a summary of the most important threads concerning friendship in the Old Testament and the Ancient Near East.